Advances in research on risk factors and associated diseases of intrapancreatic fat deposition - LEICHAO Wenwei, RAO Jialing, ZHOU Mengxue, YANG Hong (Zhenduanxue lilun yu shijian)
Intrapancreatic fat deposition (IPFD) is defined as the diffuse accumulation of fat within the pancreas. A related term, fatty pancreas (FP), refers to an IPFD fat content of ≥9.5%, which exceeds the normal upper limit. Changes in pancreatic fat content have been shown to affect at least 16% of the global population. Known risk factors for IPFD include demographic characteristics (age, sex, ethnicity), dietary patterns, obesity and metabolic syndrome, non-alcoholic fatty liver disease (NAFLD), metabolic dysfunction-associated steatotic liver disease (MASLD), metabolic dysfunction-associated fatty liver disease (MAFLD), iron overload, genetic disorders, pancreatic duct obstruction, and other potentially related conditions such as bacterial/viral infections, polycystic ovary syndrome, thyroid disorders. Accumulating evidence has established IPFD as a critical risk factor for the pathogenesis and progression of pancreatitis, pancreatic cancer, and diabetes mellitus; additionally, emerging evidence suggests its potential involvement in pancreatic fistula, post-transplant rejection, and atherosclerosis. Currently, the diagnosis of IPFD primarily relies on imaging techniques. With the rapid development of artificial intelligence (AI), AI-assisted imaging is expected to provide more accurate and comprehensive diagnostic tools for IPFD in the near future. Common intervention strategies for IPFD include lifestyle modifications (such as weight loss, dietary optimization, and regular physical activity), pharmacological treatments, and bariatric surgery. Currently, the understanding of IPFD is still unclear, so a review of the risk factors, diagnosis, harms, and intervention measures for IPFD would help improve clinical awareness of IPFD.